2019
DOI: 10.1111/jnc.14789
|View full text |Cite
|
Sign up to set email alerts
|

Post‐ischemic salubrinal administration reduces necroptosis in a rat model of global cerebral ischemia

Abstract: Ischemic stroke is one of the most important causes of death and disability worldwide. Subroutines underlying cell death after stroke are largely unknown despite their importance in the design of novel therapies for this pathology. Necroptosis, a recently described form of regulated cell death, has been related with inflammation and, in some models, with endoplasmic reticulum (ER) stress. We hypothesize that alleviation of ER stress following a salubrinal treatment will reduce the ischemic‐dependent necroptosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 53 publications
0
13
0
Order By: Relevance
“…The ratio of Sal to 4E1RCat for experimentation was based on the published literature. Specifically, Sal at 1 mg/kg has been used by multiple groups for its ability to inhibit tumor xenografts (28) and other pharmacological activities (29)(30)(31). However, 4E1RCat was not well-studied in mouse models, and hence, the dose of Sal was fixed and 4E1RCat varied to assess and maximize the combined effect.…”
Section: Animal Studiesmentioning
confidence: 99%
“…The ratio of Sal to 4E1RCat for experimentation was based on the published literature. Specifically, Sal at 1 mg/kg has been used by multiple groups for its ability to inhibit tumor xenografts (28) and other pharmacological activities (29)(30)(31). However, 4E1RCat was not well-studied in mouse models, and hence, the dose of Sal was fixed and 4E1RCat varied to assess and maximize the combined effect.…”
Section: Animal Studiesmentioning
confidence: 99%
“…Western blotting was performed at 7 days post TBI according to an established method (Li et al 2013) (Font-Belmonte et al 2019Shinozaki et al 2019). Briefly, equal amounts of protein from rat hippocampi were separated by 12% sodium dodecyl sulfatepolyacrylamide gel (BioVision) and transferred to nitrocellulose membranes (Millipore, USA).…”
Section: Western Blottingmentioning
confidence: 99%
“…Therefore, Sal can reduce ERS overexpression and block the initiation of the apoptotic program by selectively inhibiting the dephosphorylation of the PERK-eIF2α phosphate complex ( Boyce et al, 2005 ). Sal plays a cytoprotective role during ERS in various diseases ( López-Hernández et al, 2015 ; Matsuoka and Komoike, 2015 ; Font-Belmonte et al, 2019 ). Our previous studies revealed ( Zhang et al, 2015 , 2020 ) that Sal treatment improved neurological dysfunction through the inhibition of ER stress after postresuscitation brain injury.…”
Section: Introductionmentioning
confidence: 99%